HISTOPATHOLOGICAL OVERVIEW OF NEW ZEALAND WHITE PSEUDO-PREGNANT RABBIT UTERUS AFTER OVARY TRANSPLANTATION WITH VARYING DURATION OF OVARIES INSIDE THE UTERUS - Nazaruddin, Nazaruddin; Fadillah, Nurul Aini; Melia, Juli; Thasmi, Cut Nila; Roslizawaty, Roslizawaty; Sayuti, Arman; Daud, Razali; Adam, Mulyadi; Syafruddin, Syafruddin (Universitas Syiah Kuala, 2023)
This study aims to understand the histopathological changes in the pseudo-pregnant rabbit uterus concerning the duration of ovaries inside the uterus during ovarian transplantation. The study used nine New Zealand White (NZW) pseudo-pregnant female rabbits aged 3-5 years, weighed 1.5-2.9 kg. After a 30-day adaptation period, all rabbits were divided into three treatment groups: K1 (n=3) underwent ovarian transplantation for 3 days, K2 (n=3) for 5 days, and K3 (n=3) for 7 days. Pseudo-pregnant was induced using PMSG and hCG. The rabbits were intramuscularly injected with 100 IU of PMSG, followed by intravenous injection of 75 IU of hCG three days later. Ovary transplantation was performed on the 8th day (day 0 being the day of hCG injection). Uterus was collected after the transplantation procedure according to the respective treatment groups. The results showed that in K1, K2 and K3, there was hyperemia in the endometrial epithelium and infiltration of inflammatory cells. Hyperemia and necrosis were more severe in K1 compared to K2 and K3. In K3, the histopathological appearance of the endometrium tended to be normal, with less damage. In conclusion, the histopathological findings of hyperemia and necrosis in the uterus undergoing ovarian transplantation lasted for 3 days compared to 5 and 7 days.